Blended Learning and its Influence on Improving Student Literacy Competencies - Ansori (Tarsib: Jurnal Program Studi PGMI, 2025)
This research aims to analyze the effect of implementing blended learning on increasing student literacy competence at Kulon City 1 Bondowoso State Elementary School. The research method used was quasi-experimental with a Pre-test-Post-test control group design. The research sample consisted of two groups: an experimental group that applied blended learning and a control group that used conventional learning methods, each consisting of 30 students. Data was collected through a literacy test and analyzed using descriptive statistics and the independent sample t-test. The results showed that there was a significant increase in students’ literacy scores in the experimental group compared to the control group (p < 0.05). The experimental group experienced an average increase in score of 20.34 points, while the control group only increased 6.66 points. The implementation of blended learning has proven effective in supporting the development of literacy skills, especially in the aspects of critical reading and argumentative writing. In addition, blended learning provides greater benefits for students with low initial abilities through a flexible and interactive learning approach. This research confirms that blended learning is an innovative solution in improving students’ literacy competencies in elementary schools. For program sustainability, strengthening technological infrastructure and teacher training is needed. Further studies are recommended to explore the long-term impact of blended learning as well as its application to various subjects.